Utilization of Jackfruit (Artocarpus heterophyllus) Seed as a Bread Spread - Supit, Ellen Grace; Caparida, Merry Chris H.; Retutar, Warlito G.; Balagtas, Maribel; Taclan, Lorcelie; Laborde, Gladys; Oasan, Ruchel; Estrada, Miriam R. (11th International Scholars Conference, 2018)
Jackfruit is the largest tree-borne fruit in the world. It is a widely cultivated and well-consumed fruit in the Philippines and other parts of South-east Asia. The seed makes up 15-18% of the fruit weight. However, the seeds are underutilized due to the lack of information about its nutritional and food product potential. Hence, the purpose of this research was to utilize the jackfruit seed as a bread spread that is nutritious, affordable, and acceptable in terms of consistency, texture, aroma and taste. The standardized recipe for the jackfruit seed spread was obtained after three trial formulations. The jackfruit seeds were cleaned and boiled for 30 minutes, then mixed with jackfruit rags, raw sugar, olive oil, lemon juice, lemon rind, turmeric powder, and salt in a blender until a paste-like consistency and smooth texture was achieved. The blended ingredients were cooked in low heat for 15 minutes to remove excess moisture, increase shelf-life, and attain a spreadable consistency. The final product was placed in sterile airtight jars. The jackfruit seed spread has the following characteristics: canary yellow color, smooth texture, lemony aroma, and sweet acidulous taste. One serving (21g) provides 82 kcal and is a source of potassium (59mg), phosphorus (8mg), calcium (26mg), magnesium (4mg), thiamin (0.02mg), riboflavin (0.02mg), niacin (0.2mg), and vitamin C (2mg). The product was rated as like very much by 30 evaluators from both genders using a nine-point hedonic scale. The jackfruit seed spread is affordable with a selling price of ₱58.00 for a jar of 200g net weight. The shelf-life is 30 days in refrigerator temperature. It was recommended that further studies be done on producing jackfruit seed spread for a large scale business in regions were jackfruit is widely cultivated.